China's Productivity Slowdown and Future Growth Potential - Brandt, Loren; Litwack, John; Mileva, Elitza; Wang, Luhang; Zhang, Yifan; Zhao, Luan (World Bank, Washington, DC, 2020)
China’s economy grew by an impressive 10 percent per year over four decades. Productivity improvements within sectors and gains from resource reallocation between sectors and ownership groups drove that expansion. However, productivity growth has declined markedly in recent years. This paper extends previous macro and firm-level studies to show that domestic factors and policies contributed to the slowdown. The analysis finds that limited market entry and exit and lack of resource allocation to more productive firms were associated with slower manufacturing total factor productivity growth. Earlier reforms led to state-owned enterprises catching up to private sector productivity levels in manufacturing, but convergence stalled after 2007. Furthermore, the allocation of a larger share of credit and investment to infrastructure and housing led to lower returns to capital, a rapid buildup in debt, and higher risks to growth. China’s growth potential remains high, but its long-term growth prospects depend on reversing the recent decline in total factor productivity growth.